The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1520/jfs11914j
|View full text |Cite
|
Sign up to set email alerts
|

Population Frequencies of Carbonic Anhydrase II (CA II), Esterase D (EsD), and Glyoxalase I (GLO) in the Metropolitan Birmingham, Alabama Area

Abstract: Both black and white populations from Birmingham, Alabama were analyzed for the frequencies of carbonic anhydrase II (CA II), glyoxalase I (GLO) and esterase D (EsD) isozymes. The results compared favorably with published frequencies of these genetic markers in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…While the allele frequency of GLO1*1 has a mean value of about 0.305 in Asian populations, this value is about 0.44 in European populations as shown in Meighen et al's study. [21] In the present study, frequency of GLO1*1 for Turkish population was found to be 0.373. This value is inbetween those of Asians and Europeans.…”
Section: Glo1supporting
confidence: 48%
“…While the allele frequency of GLO1*1 has a mean value of about 0.305 in Asian populations, this value is about 0.44 in European populations as shown in Meighen et al's study. [21] In the present study, frequency of GLO1*1 for Turkish population was found to be 0.373. This value is inbetween those of Asians and Europeans.…”
Section: Glo1supporting
confidence: 48%
“…Low quantities of benzoylecgonine and immunological equivalents were detected in extracts from perspiration stains, menstrual bloodstains, and hair using radioimmunoassay (311). Population frequencies were presented for ABO, Gm, Km, Le, ADA, AK, and Hp (312,314), Rhesus, M, Se, and Pep A (312), CA, 11 (312,315,316), EAP (312)(313)(314), EsD (312)(313)(314)(315), GLO 1 (312,313,315), PGM (312)(313)(314)315), and Gc (314). Population studies were conducted for transferrin (317) and HLA (318).…”
Section: Forensic Biochemistrymentioning
confidence: 99%